ITSM model for very small organisation: An empirical validation - Dávila, A.; Janampa, R.; Angeleri, P.; Melendez, K. (Institution of Engineering and Technology, 2020)
Nowadays, information technology services management (ITSM) has become strongly needed for every kind of organisations providing IT services for customers or for themselves. However, existing models (as CMMI‐SVC, ITIL or ISO/IEC 20000) are strongly difficult to implement on very small organisations. The aim of this study is to validate an ITSM model specifically proposed for small organisations, the PCPS4SVC model. This model was developed considering the needs and constraints of small organisations and was verified against reference models using process mapping. In this study, the model was validated in three small enterprises, where it was tailored and implemented. As a result, the enterprises improved their IT services operation. Finally, it was determined than PCPS4SVC is a model easy‐to‐use and adequate for small enterprises.
Keywords: Information technology services management; Small organisations; PCPS4SVC model; https://purl.org/pe-repo/ocde/ford#5.02.04